A Cost-Effectiveness Analysis of Systemic Therapy for Metastatic Hormone-Sensitive Prostate Cancer - Sung, Winnie W. Y.; Choi, Horace C. W.; Luk, Peter H. Y.; So, Tsz Him (Frontiers in Oncology, 2021)
Background Currently, approved first-line treatment options of metastatic hormone-sensitive prostate cancer (mHSPC) include (1) androgen deprivation therapy (ADT) alone, ADT plus one of the following: (2) docetaxel, (3) abiraterone, (4) enzalutamide, and (5) apalutamide. The high cost of novel androgen receptor pathway inhibitors warrants an understanding of the combinations’ value by considering both efficacy and cost. Objective This study aimed to compare the cost-effectiveness of these five treatment options in mHSPC from the US payer perspective to guide treatment sequence. Methods A Markov model was developed to compare the lifetime cost and effectiveness of these five first-line treatment options for mHSPC using outcomes data from published literature. Health outcomes were measured in life-years and quality-adjusted life-years (QALYs). Drug costs were obtained from the Veterans Affairs Pharmaceutical Catalog. We extrapolated survival beyond closure of the trials. Outcome Measurements and Statistical Analysis Life-years, QALYs, lifetime costs, and incremental cost-effectiveness ratios (ICERs) were estimated. Univariable, 2-way, and probabilistic sensitivity analyses were performed to evaluate parameter uncertainty. A willingness-to-pay (WTP) threshold of US100,000 per QALY was used. Results Compared to ADT alone, docetaxel plus ADT provided a 0.28 QALY gain at an ICER of US12,870 per QALY. Abiraterone plus ADT provided an additional 1.70 QALYs against docetaxel plus ADT, with an ICER of US38,897 per QALY. Compared to abiraterone plus ADT, enzalutamide plus ADT provided an additional 0.87 QALYs at an ICER of US509,813 per QALY. Apalutamide plus ADT was strongly dominated by enzalutamide plus ADT. Given the WTP threshold of US100,000 per QALY, abiraterone plus ADT represented high-value health care. Conclusions Abiraterone plus ADT is the preferred treatment option for men with mHSPC at a WTP threshold of US100,000 per QALY.